Myeloid-derived suppressor cell accumulation and function in patients with newly diagnosed glioblastoma - Raychaudhuri, Baisakhi; Rayman, Patricia; Ireland, Joanna; Ko, Jennifer; Rini, Brian; Borden, Ernest C.; Garcia, Jorge; Vogelbaum, Michael A.; Finke, James (Neuro-oncology (Charlottesville, Va.), 2011)
To assess the accumulation of myeloid-derived suppressor cells (MDSCs) in the peripheral blood of patients with glioma and to define their heterogeneity and their immunosuppressive function. Peripheral blood mononuclear cells (PBMCs) from healthy control subjects and from patients with newly diagnosed glioma were stimulated with anti-CD3/anti-CD28 and T cells assessed for intracellular expression of interferon (IFN)-γ. Antibody staining of PBMCs from glioma patients and healthy donors (CD33, HLADR, CD15, and CD14) followed by 4-color flow cytometry analysis-defined MDSC levels in the peripheral blood. To assess the role of MDSCs in suppressing T cell IFNγ production, PBMCs were depleted of MDSCs using anti-CD33 and anti-CD15 antibody-coated beads prior to T cell stimulation. Enzyme-linked immunosorbent assays were used to assess plasma arginase activity and the level of granulocyte colony-stimulating factor (G-CSF). Patients with glioblastoma have increased MDSC counts (CD33+HLADR−) in their blood that are composed of neutrophilic (CD15+; >60%), lineage-negative (CD15−CD14−; 31%), and monocytic (CD14+; 6%) subsets. After stimulation, T cells from patients with glioblastoma had suppressed IFN-γ production when compared with healthy, age-matched donor T cells. Removal of MDSCs from the PBMCs with anti-CD33/CD15-coated beads significantly restored T cell function. Significant increases in arginase activity and G-CSF levels were observed in plasma specimens obtained from patients with glioblastoma. The accumulation of MDSCs in peripheral blood in patients with glioma likely promotes T cell immune suppression that is observed in this patient population. Increased plasma levels of arginase and G-CSF may relate to MDSC suppressor function and MDSC expansion, respectively, in patients with glioma.